Adapalene Inhibits Prostate Cancer Cell Proliferation In Vitro and In Vivo by Inducing DNA Damage, S-phase Cell Cycle Arrest, and Apoptosis - Nong, Hai-bin; Zhang, Ya-nan; Bai, Yi-guang; Zhang, Qiong; Liu, Ming-fu; Zhou, Quan; Shi, Zhuo-hua; Zeng, Gao-feng; Zong, Shao-Hui (Frontiers in Pharmacology, 2022)
Abstract Aims: Prostate cancer is a well-known aggressive malignant tumor in men with a high metastasis rate and poor prognosis. Adapalene (ADA) is a third-generation synthetic retinoid with anticancer properties. Herein, we investigated the anti-tumor activities and molecular mechanisms of ADA in the RM-1 prostate cancer cell line in vivo and in vitro. Methods: The effects of ADA on cell proliferation were estimated using CCK-8 and colony formation assays. The wound-healing assay and the Transwell assay were employed to examine the migratory capacity and invasion ability of the cells. Flow cytometry was utilized to evaluate the cell cycle and apoptosis, and western blotting analysis was used to probe into the expression of the associated protein. Using a mouse prostate cancer bone metastasis model, micro-CT, histomorphology, and immunohistochemical staining were used to assess the effects of ADA on bone structure tissue and tumor growth in mice. Result: ADA dramatically inhibited cell proliferation, migration, invasion ability, and stimulated S phase cell cycle arrest and cell apoptosis. Moreover, ADA could effectively regulate the expression of S-phase associated proteins and elevate the levels of DNA damage markers, p53, and p21 after ADA treatment, suggesting that the anti-tumor impact of ADA was facilitated by the DNA damage/p53/p21 pathway. Furthermore, we observed that ADA could effectively inhibit tumor growth and bone destruction in mice. Conclusion: ADA inhibited the proliferation, migration, and invasion of RM-1 prostate cells, arrested the cell cycle in the S phase, and elicited apoptosis through the DNA damage p53/p21 pathway. Overall, our results suggest that ADA may be a novel target or potential anticancer drug for prostate cancer.